2009
DOI: 10.1186/1471-2164-10-342
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of rat left ventricles reveals persisting changes following chronic mild exercise protocol: implications for cardioprotection

Abstract: BackgroundEpidemiological studies showed that physical exercise, specifically moderate lifelong training, is protective against cardiovascular morbidity and mortality. Most experimental work has focused into the effects and molecular mechanisms underlying intense, rather than mild exercise, by exploring the acute effect of training. Our study aims at investigating the cardioprotective effect of mild chronic exercise training and the gene expression profile changes at 48 hrs after the exercise cessation. Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Exercise has been shown to mimic ischemic preconditioning and also lead to cardiac protection (38). Gene expression profiles of rat left ventricles after mild exercise showed elevated mRNA levels of cAMP response element binding protein (plausibly PKA-regulated), AKIP1, and HIF1α (39). Such findings are consistent with our observations and suggest that overexpression of AKIP1 may be a therapeutic approach for limiting cardiac injury.…”
Section: Discussionsupporting
confidence: 81%
“…Exercise has been shown to mimic ischemic preconditioning and also lead to cardiac protection (38). Gene expression profiles of rat left ventricles after mild exercise showed elevated mRNA levels of cAMP response element binding protein (plausibly PKA-regulated), AKIP1, and HIF1α (39). Such findings are consistent with our observations and suggest that overexpression of AKIP1 may be a therapeutic approach for limiting cardiac injury.…”
Section: Discussionsupporting
confidence: 81%
“…Our data suggests that caveolins may be an intrinsic factor involved in the cardiac response to exercise via their multiple interactions with ion channels and other cell signaling molecules. Previous investigations have shown that Cav-3 mRNA is up regulated in trained animal hearts approximately 2-fold [18]. Interestingly, our Cav-3 OE mice have an approximate 2-fold elevation of Cav-3 protein at baseline [55].…”
Section: Discussionmentioning
confidence: 73%
“…The possible involvement of HIF-1 in exercise-induced cardioprotection was recently demonstrated by Giusti et al [66] . In a rat model of chronic exercise-induced cardioprotection, these researchers found that HIF-1α was among the genes that were significantly upregulated in the left ventricular tissues 48 hours after the last training session of the 10-week mild intensity aerobic exercise protocol.…”
Section: Hif-1 and Excercise-induced Cardioprotectionmentioning
confidence: 79%
“…Volatile anesthetics are known to produce pharmacological [23] Xi et al, 2004 [17] Ockaili et al, 2005 [48] Date et al, 2005 [58] Kido et al, 2005 [62] Natarajan et al, 2006 [53] Natarajan et al, 2008 [55] Luciano et al, 2008 [50] Raphael et al, 2008 [45] Myocardial infarct size; cardiac function; kidney EPO mRNA expres sion; Plasma EPO levels [33] Eckle et al, 2008 [34] Tan et al, 2009 [51] Rane et al, 2009 [61] Czibik et al, 2009 [59] Giusti et al, 2009 [66] Hyvarinen et al, 2010 [64] Bao et al, 2010 [52] Myocardial infarct size; cardiac function; apoptosis; impaired mitochondrial ROS production, PTEN oxidation and AKT phos phorylation in heterozygous HIF-1α knockout mice…”
Section: Volatile Anestheticsmentioning
confidence: 99%